Knowledge and attitudes towards Alzheimer’s disease among adult residents in Jiulongpo, Chongqing, China: A cross-sectional survey - Jinhua Zhang; Yao Huang; Yi Jiang; Tong Li (PLoS ONE, 2025)
Background The prevalence of Alzheimer’s disease (AD) continues to rise as the aging population increases, and the resulting cognitive decline severely affects patients’ quality of life. However, the public’s understanding of AD is markedly insufficient, which limits the effectiveness of early prevention and treatment. This study conducted a cross-sectional survey to assess the level of knowledge about AD among adult residents in Jiulongpo District, Chongqing, as well as their attitudes towards people with dementia, providing a basis for formulating targeted intervention strategies. Methods A cross-sectional survey was conducted in Jiulongpo, Chongqing, China, from September to October 2024. The self-reported questionnaire for participants included three parts: demographic information, the Alzheimer’s Disease Knowledge Scale (ADKS), and the Dementia Attitude Scale (DAS). Multiple linear regression analysis was used to identify the main factors influencing AD knowledge and attitudes. Results 1,362 respondents were surveyed, with 64.24% female. The age group of 40–64 has the largest number of people, accounting for 38.03%. The average ADKS score was 17.67 (standard deviation = 2.47), with individual item score rates ranging from 16.01% to 89.72% across the 30 items. The domains with the lowest ADKS score rates were “Caregiving” (43.40%) and “Symptoms” (52.25%). The average score on the DAS was 81.72 (standard deviation = 11.19). The score rates for the “Dementia knowledge,” “Positive social comfort,” and “Negative social comfort” dimensions of the DAS were 61.56%, 55.02%, and 56.38%, respectively. Residents aged 18–39, living in urban areas, with higher education or above, working in healthcare, having a higher income level, being unmarried, and having experience in Alzheimer’s Disease and Related Dementias (ADRD) knowledge training have a higher level of knowledge about AD and a more positive attitude towards it. Residents with family members suffering from ADRD have lower DAS scores than those without such family members. Conclusion People’s understanding of AD is limited, especially in the areas of “Caregiving” and “Symptoms”, and they hold a neutral attitude toward dementia. We recommend intensifying health education efforts on AD knowledge across different populations, particularly emphasizing the promotion of knowledge in weak areas, while also cultivating their friendly attitudes towards dementia patients.